2007
DOI: 10.1210/jc.2007-0527
|View full text |Cite
|
Sign up to set email alerts
|

Random Variability in Congenital Hypothyroidism from Thyroid Dysgenesis over 16 Years in Québec

Abstract: The incidence of CHTD did not vary over the observation period, and its monthly variation was random. Therefore, environmental factors do not appear to play a significant role in the etiology of CHTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 20 publications
4
59
2
3
Order By: Relevance
“…An increasing temporal trend in incidence of CHT has recently been reported in New However, this is in contrast to research conducted in Quebec, Canada, where no changes in incidence were seen over a 16 year period [4]. A real temporal trend, aside from changes in diagnostic procedures which can lead to increases in incidence [25], suggests either an increasing exposure to an environmental risk factor, or a changing distribution of risk factors among the population.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…An increasing temporal trend in incidence of CHT has recently been reported in New However, this is in contrast to research conducted in Quebec, Canada, where no changes in incidence were seen over a 16 year period [4]. A real temporal trend, aside from changes in diagnostic procedures which can lead to increases in incidence [25], suggests either an increasing exposure to an environmental risk factor, or a changing distribution of risk factors among the population.…”
Section: Discussionmentioning
confidence: 81%
“…An increasing incidence of CHT has been suggested from an analyses of data including that from New York State [2] and Mexico [3], although no similar increase was shown in a similar study of data from Quebec [4]. Previous studies in the United Kingdom have suggested that CHT is more prevalent in Asian sectors of the population and that prevalence has increased [5].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…A role of environmental factors affecting thyroid development is, however, still largely hypothetical. On the contrary, the lack of a seasonal variation argues against a significant contribution of the environment (Deladoey et al 2007a). The genetic basis of TD was recently emphasized by the finding of gene copy number variations in 9% of a patient cohort (Thorwarth et al 2010).…”
Section: What Can We Learn From Patients?mentioning
confidence: 99%